2014
DOI: 10.1186/1475-2867-14-16
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptor activation induces apoptosis of melanoma cell through caspase pathway

Abstract: Liver X receptors (LXRs) are nuclear receptors that function as ligand-activated transcription factors regulating lipid metabolism and inflammation. Recent discoveries found LXRs could regulate tumor growth in a variety of cancer cell lines. In this study, we investigated the effect of LXR activation on melanoma cell proliferation and apoptosis both in vitro and in vivo. Treatment of B16F10 and A-375 melanoma cells with synthetic LXR agonist T0901317 significantly inhibited the proliferation of melanoma cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Further, there are data suggesting that this oxysterol can inhibit HMGCR activity in an indirect fashion, although the mechanism behind this activity is unclear [50]. Based on this established biology it was expected that 27HC would inhibit the growth of cancer cells, as has been observed for other LXR agonists [5153]. However, recent studies have shown that 27HC actually promotes the proliferation of ER-positive breast cancer cell lines, in vitro [42, 54].…”
Section: -Hydroxycholesterol and Breast Cancermentioning
confidence: 99%
“…Further, there are data suggesting that this oxysterol can inhibit HMGCR activity in an indirect fashion, although the mechanism behind this activity is unclear [50]. Based on this established biology it was expected that 27HC would inhibit the growth of cancer cells, as has been observed for other LXR agonists [5153]. However, recent studies have shown that 27HC actually promotes the proliferation of ER-positive breast cancer cell lines, in vitro [42, 54].…”
Section: -Hydroxycholesterol and Breast Cancermentioning
confidence: 99%
“…LXR agonists can disrupt the proliferation of several cell types via altering expression levels of genes involved in controlling cell cycle and reduce angiogenesis in pathological conditions of uncontrolled angiogenesis . Recently, accumulating evidence indicates the important functional role of LXRs in a variety of malignancies, affecting both tumor growth and tumor metastasis . For example, the synthetic ligand T0901317 can inhibit prostate cancer cell proliferation and tumor formation and overexpression of LXRα can sensitize cancer cells to the ligand .…”
mentioning
confidence: 99%
“…Whereas 27HC may have several functions within cells its role as an LXR agonist which inhibits cholesterol production and increases cholesterol efflux from cells is very well established. Thus, it would be expected, as has been observed for other LXR agonists, that 27HC would inhibit the growth of cancer cells (44-46). However, we and others have shown that 27HC actually promotes the proliferation of ER-positive, but not ER-negative, breast cancer cell lines in vitro (29) .…”
Section: Hormonal Actions Of 27-hydroxycholesterol In Breast Cancermentioning
confidence: 81%